Charitable giving to college athletics: the role of brand communities in choosing how much to give. Issue 1 (2nd January 2021) - Kelly, Deborah; Vamosiu, Adriana
ABSTRACT: The literature on charitable contributions to higher education focuses overwhelmingly on why donors give. This study aims to understand the monetary choice of a contribution, specifically what factors are linked to higher/lower donations. The current research employs the brand communities framework to analyze the role of the strength of the bonds between all types of donors, the collegiate athletics teams they support and their respective department, as it pertains to the level of charitable contributions to collegiate athletics. Considering these relationships explicitly allows for a comprehensive analysis of both the demand and supply side of this market. Ordinal logistic regressions reveal that athletics sponsored donor events are associated with higher contributions from those attending. Fundraising campaigns detailing the specific needs of the teams are met with higher donations. Benefactors attending college sports games are linked to higher contributions. The winning record of a team is associated with gift size for a subsample of contributors only. The econometric technique allows ranking marketing strategies relative to size of contribution, information essential in developing one's brand community development plan. As fluctuations in the economy have rippling effects in philanthropy, the practical implications are relevant to collegiate and other nonprofit athletics advancement and marketing professionals.